The Charter versus the Government’s Crime Agenda - Roach, Kent (2012)
The Safe Streets and Communities Act, like many other parts of the government’s crime agenda, relies on both prosecutorial discretion and a general judicial reluctance to strike down mandatory sentences. Successful Charter challenges to mandatory sentences are not impossible, as seen by Molloy J.’s recent decision in Smickle, but they will be difficult. In particular, the use of reasonable hypotheticals in section 12 analysis may be precluded by reliance on the assumption that longer mandatory sentences will not be applied when the Crown has the power to avoid such sentences by electing to prosecute the relevant crime by way of more lenient summary conviction procedures. Courts will the n be reluctant to review Crown elections as exercises of prosecutorial discretion. The Supreme Court will ultimately have to decide whether it wishes to maintain the level of judicial deference towards mandatory sentences that it has demonstrated in the past. This paper argues that a more traditional approach to proportionality that focuses on the relationship between particular crimes and punishment is more promising than newer approaches based on arbitrariness in relation to legislative purposes or gross disproportionality in the costs and benefits of legislative interventions, as conducted in the Insite case and Bedford. Following Smith and Ipeelee, a contextual approach to proportionality between crime and punishment that factors in offender characteristics should be taken rather than the more abstract approach taken in Morrisey. Should mandatory sentences be found to violate either section 7 or section 12 of the Charter, they will be difficult to justify under section 1. Policy analysis about the necessity and effects of mandatory sentences is best conducted under section 1 rather than within sections 7 and 12